METHODOLOGY FOR DEVELOPING TECHNICAL PREPARATION IN PARALYMPIC JUDO ATHLETES BASED ON THE REQUIREMENTS OF THE DEVELOPMENT STRATEGY (Ideal Journal of Multidisciplinary Research, 2026)
This article examines the methodology for developing technical preparation in Paralympic judo athletes in accordance with the requirements of the Development Strategy, which prioritizes the expansion of inclusive sports, the improvement of adaptive training systems, and the strengthening of athletes’ competitive capacity. In Paralympic judo, technical preparation is not limited to the mechanical acquisition of throws, grips, balance control, and transition movements, but also includes the adaptation of these elements to the functional abilities, sensory characteristics, and competitive conditions of athletes with visual impairments. The study is based on the idea that an effective methodology should combine pedagogical consistency, differentiated instruction, safety principles, and systematic progression from basic motor patterns to complex technical combinations. Particular attention is given to the role of specialized drills, tactile orientation, paired interaction, repeated situational practice, and correctional feedback in improving technical mastery. The article argues that the formation of technical preparation becomes more effective when training is organized through stage-based planning, individualized load distribution, and continuous assessment of movement accuracy and stability. It is concluded that a scientifically grounded methodology for technical preparation in Paralympic judo contributes to higher performance quality, greater training efficiency, and broader realization of strategic objectives related to inclusive physical culture and sports development.
Keywords: Paralympic judo, technical preparation, training methodology, adaptive sports, inclusive education, motor skills, tactile orientation, competitive performance, differentiated instruction, sports training, movement coordination, athlete development.